2022
DOI: 10.1001/jamapsychiatry.2022.2862
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Standard Sequential Bilateral Repetitive Transcranial Magnetic Stimulation vs Bilateral Theta Burst Stimulation in Older Adults With Depression

Abstract: ImportanceTreatment-resistant depression (TRD) is common in older adults. Bilateral repetitive transcranial magnetic stimulation (rTMS) of the dorsolateral prefrontal cortex for 48 minutes has demonstrated efficacy in TRD. Theta burst stimulation (TBS), a newer form of rTMS, can also be delivered bilaterally using left intermittent TBS and right continuous TBS for only 4 minutes.ObjectiveTo establish the effectiveness and tolerability of TBS compared with standard rTMS in older adults with TRD.Design, Setting,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…In contrast, the sequential bilateral approach of inhibitory stimulation (1 Hz) to the right DLPFC and excitatory stimulation (10 Hz) to the left DLPFC has demonstrated efficacy with standard rTMS 54,55 and theta burst (continuous TBS right and iTBS left) 56 and has recently shown efficacy in older adults. 57,58 Notwithstanding the large effect in the sham group, the lower than expected depression response to active stimulation may reflect an unintended suppression of the antidepressant effects related to the excitatory stimulation of the right DLPFC.…”
Section: Association Between Brain Network Engagement and Change In D...mentioning
confidence: 98%
“…In contrast, the sequential bilateral approach of inhibitory stimulation (1 Hz) to the right DLPFC and excitatory stimulation (10 Hz) to the left DLPFC has demonstrated efficacy with standard rTMS 54,55 and theta burst (continuous TBS right and iTBS left) 56 and has recently shown efficacy in older adults. 57,58 Notwithstanding the large effect in the sham group, the lower than expected depression response to active stimulation may reflect an unintended suppression of the antidepressant effects related to the excitatory stimulation of the right DLPFC.…”
Section: Association Between Brain Network Engagement and Change In D...mentioning
confidence: 98%
“…Notably, although three articles compared the e cacy of TBS and rTMS, they were not included because of their retrospective design [25,39,40]. After the selection procedure, nine eligible RCTs comparing the e cacy of TBS to rTMS for treating MDD were nally selected [17,23,[41][42][43][44][45][46][47]. Among them, Chen et al (2021) included two sets of comparable trials [43], namely, 10 Hz rTMS vs. low-intensity (80% RMT) TBS and 10 Hz rTMS vs. high-intensity (120% RMT) TBS.…”
Section: Page 4/13mentioning
confidence: 99%
“…Among the eight eligible RCTs, two were conducted in Canada [17,41], two in Australia [43,45], two in China [23,44], and one each in France [42], Britain [46],…”
Section: Study Featuresmentioning
confidence: 99%
“…However, the effect of accelerated thetaburst stimulation (TBS) in patients with PTSD and depression remains unclear. Previous studies have demonstrated antidepressant effects of bilateral TBS (left sided iTBS + right sided cTBS) in the treatment of major depression (18)(19)(20). However, due to that patient's urgent clinical status, we needed to improve her condition rapidly.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have demonstrated antidepressant effects of bilateral TBS (left sided iTBS + right sided cTBS) in the treatment of major depression ( 18 20 ). However, due to that patient's urgent clinical status, we needed to improve her condition rapidly.…”
Section: Introductionmentioning
confidence: 99%